IMPROVING LISTENING SKILL THROUGH PODCAST (Modern education and development, 2024)
The purpose of this study is to discover the use of podcasts in improving students’ listening skills. The quantitative technique was used in this research. Podcasting is one such novel tool being exploited by teachers to enhance language skills and to encourage learning outside the classroom. Research on podcasting pedagogy suggests that podcasting helps learners boost their English language skills and support areas such as grammar, pronunciation and vocabulary.  Overall, this study suggests that developing English listening skills can be boosted with Podcasts.